2016
DOI: 10.1089/dna.2016.3422
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNA HOXC-AS1 Suppresses Ox-LDL-Induced Cholesterol Accumulation Through Promoting HOXC6 Expression in THP-1 Macrophages

Abstract: Atherosclerosis is a common pathological basis of cardiovascular disease, which remains the leading cause of mortality. Long noncoding RNAs (lncRNAs) are newly studied non-protein-coding RNAs involved in gene regulation, but how lncRNAs exert regulatory effect on atherosclerosis remains unclear. In this study, we found that lncRNA HOXC cluster antisense RNA 1 (HOXC-AS1) and homeobox C6 (HOXC6) were downregulated in carotid atherosclerosis by performing microarray analysis. The results were verified in atherosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 33 publications
2
36
0
1
Order By: Relevance
“…Our initial quantitative real‐time RT‐PCR (qPCR) analysis included atherosclerosis‐ or cardiac‐related lncRNAs: lncRNA KCNQ1 opposite strand/antisense transcript 1 (KCNQ1OT1), hypoxia‐inducible factor 1 alpha‐antisense RNA2 (HIF1A‐AS2) and apolipoprotein A‐1 antisense RNA (APOA1‐AS) . As illustrated, the three lncRNAs were significantly higher in PBMC samples from CAD patients than in those from healthy subjects.…”
Section: Resultsmentioning
confidence: 99%
“…Our initial quantitative real‐time RT‐PCR (qPCR) analysis included atherosclerosis‐ or cardiac‐related lncRNAs: lncRNA KCNQ1 opposite strand/antisense transcript 1 (KCNQ1OT1), hypoxia‐inducible factor 1 alpha‐antisense RNA2 (HIF1A‐AS2) and apolipoprotein A‐1 antisense RNA (APOA1‐AS) . As illustrated, the three lncRNAs were significantly higher in PBMC samples from CAD patients than in those from healthy subjects.…”
Section: Resultsmentioning
confidence: 99%
“…Gene chips and other high-throughput sequencing tools have received increasing attention, especially in cancer research. Huang [ 15 ] found that lncRNA HOXC-AS1 and HOXC6 were down-regulated in carotid atherosclerosis by microarray analysis. Singh [ 22 ] assessed the expression profiles of lncRNAs and protein-coding mRNAs in endothelial cells 24 hours after stimulation of oxidized low-density lipoprotein (100 μg/mL) with Arraystar human lncRNA expression microarray V3.0.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that lncRNA HOXC-AS1 can be perceived as a method of therapy for atherosclerosis. [ 15 ] Previous studies have shown that lncRNAs can be important regulators of cell apoptosis, proliferation, and differentiation of ECs and VSMCs. [ 16 18 ] Although previous studies involved some noncoding RNAs, the exact mechanisms of atherosclerosis and lncRNAs were largely unknown until now.…”
Section: Introductionmentioning
confidence: 99%
“…One of the upregulated lncRNAs, lincRNA-DYNLRB2-2, was shown to promote ATP-binding cassette transporter A1 (ABCA1)-mediated cholesterol efflux from THP-1 macrophage-derived foam cells, and inhibit the inflammatory response ( Figure 4 C ) 101 . LncRNA HOXC cluster antisense RNA 1 (HOXC-AS1) and its nearby gene HOXC6 were downregulated by Ox-LDL in THP-1 cells, and reduced in renal arterial intima tissues and advanced atherosclerotic plaques in patients 102 . Lentivirus-mediated overexpression of HOXC-AS1 induced HOXC6 expression, and suppressed the induction of cholesterol accumulation by Ox-LDL, suggesting a protective role for HOXC-AS1 in atherosclerosis ( Figure 4 D ).…”
Section: Lncrnas In Vascular Diseasementioning
confidence: 99%